Fijian Farmers' Attitude and Knowledge Towards Antimicrobial Use and Antimicrobial Resistance in Livestock Production Systems–A Qualitative Study - Khan, Xavier; Lim, Rosemary H. M.; Rymer, Caroline; Ray, Partha (Frontiers in Veterinary Science, 2022)
Antimicrobial resistance (AMR) is a global health issue affecting humans and livestock. To mitigate AMR risks, responsible use of antimicrobials in livestock production systems have been advocated. Studies have reported patterns of antimicrobial use (AMU) in livestock production systems; however, there is limited information on the drivers of AMU and AMR. Therefore, this study aimed to explore and understand the attitude and knowledge of Fijian livestock farmers on AMU and AMR. Livestock farmers and managers from the Central and Western divisions of Viti Levu, Fiji were recruited using purposive and snowball sampling methods. Face-to-face one-to-one semi-structured qualitative interviews were conducted. Interview questions were informed by the Theory of Planned Behaviour (TPB). Interview transcripts were analysed inductively using reflexive thematic analysis and deductively using the TPB framework. A total of 19 participants took part. Our analysis generated four themes: 1) Uninformed use of antimicrobials and unaware of AMR, 2) Safeguarding livestock and generating income source as primary motivators for using antimicrobials 3) Medicine shortage results in hoarding and self-prescribing, and 4) Farm decisions on AMU and livestock management influenced by foreign farmers and veterinarians. Livestock farmers used medicines in livestock production; however, they could not differentiate amongst different types of medicine, including antimicrobials. Antimicrobials were used to prevent diseases in livestock and promote production for food and financial security but without any awareness of the risks of AMR. Additionally, farmers hoarded and self-prescribed medicines. Farmers rationed antimicrobials by not completing the entire course of antibiotics to save them for future use. Based on past experiences, farmers expressed dissatisfaction with the veterinary services provided by the government. They sought help online and from foreign farmers and veterinarians. We propose the need for antimicrobial stewardship (AMS) programmes focused on promoting rational use of antimicrobials and awareness of AMR amongst farmers in the Fijian livestock production systems. These programmes need to consider the anthropological, socio-cultural, economic, and environmental factors driving AMU. Future studies are underway to explore the attitude and knowledge of Fijian veterinarians, para-veterinarians and pharmacists on AMU and AMR to gain a broader systems knowledge to inform the design of AMS programmes.